An annotated catalog of the Iranian Cimicidae and Largidae (Hemiptera: Heteroptera) and in memoriam Carl Walter Schaefer (1934–2015) - Ghahari, Hassan; Moulet, Pierre; Ostovan, Hadi (Zootaxa, 2016)
The Iranian fauna of the Cimicidae and Largidae (Hemiptera: Heteroptera) is summarized in this paper. In total, 2 species from 2 genera of Cimicidae and single species of Largidae are listed.